2013
DOI: 10.5539/jas.v5n6p25
|View full text |Cite
|
Sign up to set email alerts
|

Entomophagy: A Panacea for Protein-Deficient-Malnutrition and Food Insecurity in Nigeria

Abstract: The paper posits that Nigeria like most developing countries is not immune to protein deficiency among its population because of the often prohibitive prices and overdependence on conventional animal protein source which are in limited supply. The consumption of edible insects is a way out of this predicament. Entomophagy is common practice in the tropics only varying with location, insect(s) consumed, and ethnic group. Again, it posits that insects as a source of protein is better than many conventional sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…a lack of protein and energy foods), principally resulting from the fact that people do not eat domestic animals (except chickens and other animals during sacrifice). Furthermore, there is a shortage of rice during the planting season but also too much time invested in field work, limiting the search for other sources of energy …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…a lack of protein and energy foods), principally resulting from the fact that people do not eat domestic animals (except chickens and other animals during sacrifice). Furthermore, there is a shortage of rice during the planting season but also too much time invested in field work, limiting the search for other sources of energy …”
Section: Introductionmentioning
confidence: 99%
“…In an exploratory investigation in Ratanakiri Province, people from the Annâdya Project have shown that 65% of the participating villagers ( n = 30) were interested in developing cricket breeding (Annâdya Project, personal communication). Effectively, the development of insect farming would be a more economic and time efficient and environmentally safer way to generate a continuous supply of insects to indigenous people, and consequently increase household protein consumption . For example, a large farm will have about 60–80 breeding containers (2.5 × 8 × 0.5 m) with about 2–3 h of labour needed every day to feed and take care of the cricket colonies .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insects are classified as one of the most successful group of animals on earth constituting about 76% of all known species of animals; found in nearly all environments; and widely distributed across aquatic ecosystems, farm land and forests (Adegbola, Awagu, Arowora, Ojuekaiye, Anugwom and Kashetu, 2013). Ironically, they have also been rated as the most under-utilized and under exploited creature on earth by mankind in the time past (Huis, 2012).…”
Section: Introductionmentioning
confidence: 99%